2013
DOI: 10.4028/www.scientific.net/amr.686.305
|View full text |Cite
|
Sign up to set email alerts
|

Study on Fabrication of Ceramic Membrane from Shirasu Balloon for Waste Water Filtration

Abstract: The fabrication of low cost ceramic membranes for microfiltration were studied by using a natural materials (shirasu balloon) which are produced from glassy volcanic materials. The shirasu powder was formed into cylindrical shaped membranes and sintered at five different temperatures from 600 °C to 800 °C using spark plasma sintering (SPS). The porosity and density of membranes were measured according to Archimedes method. The effect of sintering temperatures on microstructure and phase of the membranes has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“… 92 The oil in water filtration of the S-sintered COK-12 monolith is more effective in comparison to S-sintered monoliths produced from volcanic shirasu balloon, which exhibit lower porosities and larger pores at comparable processing parameters. 93 Further S-sintered materials such as diatomite were suggested to be suitable for water purification applications. 94 Furthermore, the produced COK-12 monoliths may present additional benefits, such as molecule capture, due to their hierarchical pore structure from the macro-to the meso-/micropore scale.…”
Section: Resultsmentioning
confidence: 99%
“… 92 The oil in water filtration of the S-sintered COK-12 monolith is more effective in comparison to S-sintered monoliths produced from volcanic shirasu balloon, which exhibit lower porosities and larger pores at comparable processing parameters. 93 Further S-sintered materials such as diatomite were suggested to be suitable for water purification applications. 94 Furthermore, the produced COK-12 monoliths may present additional benefits, such as molecule capture, due to their hierarchical pore structure from the macro-to the meso-/micropore scale.…”
Section: Resultsmentioning
confidence: 99%
“…The raw micro balloon shows a broad diffraction peak around 44°, 36° and 27° in Figure 3(e). In regard to the XRD patterns of raw microballoons, Ahmad et al reported the peak at 26.5° and 27.8°derived from quartz, and the peak at 28.2° derived from albite [10] . Therefore, the diffractions we observed correspond to quartz.…”
Section: Results and Discussion 31 Homogeneous Precipitation Processmentioning
confidence: 99%
“…The filtration process occurs through size exclusion, sedimentation, and adsorption mechanisms. In addition to its ability to remove turbidity and pathogens, the CWF can produce clear water without changing the flavor or odor of the water. CWF can be fabricated in different geometries, making it flexible for various conditions. Another advantage of a CWF is its service life of up to 5 years, making it an affordable option for decentralized POU systems …”
Section: Introductionmentioning
confidence: 99%
“…CWF can be fabricated in different geometries, making it flexible for various conditions. 17 − 19 Another advantage of a CWF is its service life of up to 5 years, making it an affordable option for decentralized POU systems. 20 …”
Section: Introductionmentioning
confidence: 99%